Entrepreneurship, Motivation, Perception, and Performance of Micro Businesses in Makassar City - Jamil, Muh; Alam, Syamsu; Ashdaq, Muhammad; Taufik, Muhammad (PINISI Discretion Review, 2024)
This study aims to determine the motivation to become an entrepreneur, perceptions after becoming an entrepreneur and the performance of businesses run in Makassar City in 2023. Using primary data from direct interviews in the form of data on the main motivation to become an entrepreneur, experience, financing, number of employees, turnover and profit. Analyzed quantitatively descriptively. The results of the study show that the majority of entrepreneurs are forced because there is no other work but after running it the entrepreneur feels satisfied, an average turnover of 33 million rupiah with a profit level of 4.9 million per month.